(untitled) (Годишен зборник на Филозофски факултет - Скопје, 2025)
Through a summarized insight into the historical developmental stages in art and culture, this paper anticipates the hypothesis of the existence of a dialectical structure in the Macedonian art-modernist discourse, generated by the positions of the artist/ art in relation to the complex social reality in Macedonia. Since the pre-war period, the subject of analysis has been art as a social practice and the artist as a social actor (the founders of modern art, Ličenoski, Martinoski) who, through the theme of labor and the worker, provides an engaged response addressing the question of class consciousness. From the post-war period (the division of the world into blocs, the clash of East and West) as a turning point, the paper explores the potential of public speech (by Miroslav Krleža) as a call for freedom of artistic creation and as resistance to imposed dogmas (socialist realism). The step towards a decisive dialectization of art and culture is examined through the activities of the group “Denes” (a promising step), the democratization of art, and the “aesthetic pluralism” of its creators (Lazeski, Grabuloski). Post-war monumental art is analyzed through the aspect of man-society, that is, through the role of individual artistic impulses (Mazev, Čemerski) in the construction of a new social system. In a continuity of crisis historical situations, the foundation of art is guided by the need for participation in the construction of a new society, based on and constituted by the dialectical attitudes and individual decisions of modernist artists.